Phytochemical Screening, GC-MS Charecterisation and Antioxidant Activity of N-Hexane Fraction of Microtrichia perotitii DC - Nuhu, Abdullahi Maikudi; Istifanus, Istifanus; Usman, Solomon; Idris, Idris; Abdullahi, Abdullahi (Biology, Medicine, & Natural Product Chemistry, 2025)
Microtrichia perotitii DC belongs to the family Asteraceae (Compositeae) and it is an herb found in the West African countries. The herb has been used ethnomedicinally to treat children's rashes, burns, wounds, jaundice, rheumatism, diarrhea, and skin conditions. The n-hexane fraction of the ethanolic extract of the plant was investigated for the presence of secondary metabolites, characterisation as well as its antioxidant activity with a view to exploring other significant information that would be of benefit to scientific study. The n-hexane extract was subjected to partitioning, phytochemical screening using standard methods as well as spectroscopic characterizations using UV, FTIR and GC-MS analysis including antioxidant activity. The result of the phytochemical screening revealed the presence of alkaloids, tannins, saponins, phenols, glycosides, steroids, terpenoids and flavonoids, but anthraquinones and phlobatannins were absent. The spectroscopy analysis showed a high degree of conjugation and it also reveals the presence of Hydroxyl (O-H), carbonyl (C=O) and methyl (C-H) groups, with the compound, Pentadecanoic acid, 14-methyl-, methyl ester, having the highest abundance while the antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Nitric oxide (NO),radical scavenging assays exhibited antioxidant activity with an IC50 value of 4.61mg/mL but less than ascorbic acid which has an IC50 value of 0.84mg/mL. The phytochemical compounds present in the plant could be responsible for its antioxidant property which suggests the use of the plant in the treatment of diseases induced by free radicals. In the light of the importance of this herb in local applications, the research was aimed at exploring the scientific evidences to support the local claims as well as improving information of the efficacy of the plant.